Developmental Behavioral Pediatrician Support of the Medical Home for Children with Autism Spectrum Disorders. Issue 9 (November 2016) - Nolan, Robyn; Walker, Tarik; Hanson, Janice L.; Friedman, Sandra
ABSTRACT: Objective: To identify challenges primary care providers (PCPs) experience providing a Medical Home for children with autism spectrum disorders (ASDs) and to describe the role developmental behavioral pediatricians (DBPs) play in the Medical Home Neighborhood. Methods: The authors used purposeful sampling to recruit 25 PCPs from around Colorado to participate in 4 focus groups. Member checking was performed at the end of each group. Sampling continued until themes repeated and saturation was achieved. Focus groups were transcribed verbatim, and transcripts were analyzed using content analysis; an outside reviewer audited the data. Results: Qualitative analysis yielded 30 codes that fell into 7 themes: provider education, shared model of care, initial diagnostic evaluation by the DBP, communication, office factors, cost and coverage, and access. PCPs identified knowledge gaps that led to decreased comfort and desired ongoing education and a centralized resource for providers. They envisioned a shared care model with ongoing specialist collaboration and improved communication within the care team. A specific role desired of the DBP was to provide the initial diagnostic evaluation and treatment plan with specific resources. Office factors, high cost and variable coverage, and poor access to services were barriers to providing a Medical Home for children with ASD. Conclusion: Working to remove barriers to shared care as well as providing continued educational opportunities will help improve access to a Medical Home Neighborhood for children with ASD. Advocacy is needed to help remove barriers related to cost, coverage, and access to services.